(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Complete submergence up to 1-2 weeks of low land rice crops during flash floods occurs in large areas of South-East Asia including Bangladesh, resulting in increased mortality of plants as well as low productivity of rice crops. A pot experiment was conducted at the Net House, Department of Crop Botany, Bangladesh Agricultural University, Mymensingh, during Aman season from July 2017 to December 2017 to evaluate morphological and phenological traits associated with submergence tolerance in rice. The experiment consisted of two factors—Rice cultivars (Binadhan-11, Binadhan-12, BRRI dhan51 and BRRI dhan52 as tolerant and BRRI dhan49 as susceptible) and submergence stress for 14 days at vegetative stage and control. Submergence stress was imposed by dipping of pots into a water tank with about 90 cm depth of water. After desubmergence, the plants were grown with proper care till maturity. Control plants are maintained in the pot house of field laboratory. Leaf greenness was measured after desubmergence to physiological maturity. The tolerant cultivars maintain higher leaf greenness for a long time than the susceptible cultivar after desubmergence. Reduction of grain filling rate and yield was significantly higher in susceptible cultivar than the tolerant cultivars. Among the five cultivars, BRRI dhan51 contributed the highest yield under stress treatment. Submergence tolerant rice cultivars (Binadhan-11, Binadhan-12, BRRI Dhan51 and BRRI Dhan52) had maintained higher tiller number, 1000-grain weight and the higher number of grains per panicle during submergence, as compared to susceptible rice cultivar BRRI Dhan49. J Bangladesh Agril Univ 17(4): 545–550, 2019